2005
DOI: 10.1530/rep.1.00653
|View full text |Cite
|
Sign up to set email alerts
|

Follicular cysts occur after a normal estradiol-induced GnRH/LH surge if the corpus hemorrhagicum is removed

Abstract: The pathophysiology underlying follicular cysts appears to be lack of an estradiol (E 2 )-induced GnRH/LH surge due to hypothalamic insensitivity to E 2 . In addition, progesterone (P 4 ) can cause animals with follicular cysts to resume normal cyclicity and normal hypothalamic responsiveness to E 2 . We postulated that follicular cysts may be a pathological manifestation of a physiological state that cows, and possibly other species, go through during the normal estrous cycle but the rise in P 4 following ovu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…Thus, our results suggest that both dominant follicles were healthy and had an ovulatory capacity in most of the CL-absent cattle. Our present results are consistent with a recent study in which the high incidence of co-dominant follicles was observed in the contralateral remaining ovary when the corpus haemorrhagicum was removed soon after ovulation (Gumen & Wiltbank 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our results suggest that both dominant follicles were healthy and had an ovulatory capacity in most of the CL-absent cattle. Our present results are consistent with a recent study in which the high incidence of co-dominant follicles was observed in the contralateral remaining ovary when the corpus haemorrhagicum was removed soon after ovulation (Gumen & Wiltbank 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The specific times were chosen because a diameter of 7.8-8.0 mm represents a time approximately 8-12 h before follicular deviation; therefore, it was expected that the 12-h time point would be close to the expected time of deviation and the 24-h time point approximately 12-16 h after deviation. Ovariectomy was performed using the colpotomy technique [26] at 12 and 24 h after acyline (or saline) treatment using an ecraseur (Jorgensen Laboratories, Inc.).…”
Section: Animal Procedures and Experimental Designmentioning
confidence: 99%
“…In relation to endocrine signaling pathways, some of these studies have demonstrated altered expression of steroid and gonadotropin receptors , Marelli et al 2014. Other studies have postulated and tested the intrafollicular roles of steroids in regulating follicular development (Berisha et al 2002, Gümen & Wiltbank 2005.…”
Section: Introductionmentioning
confidence: 99%